Low back pain among office workers in a public university in Malaysia - Damanhuri, Zulhusni; Zulkifli, Adilah; Lau, A. C. T.; Zainuddin, Huda (Community Health Society Malaysia, 2014)
Introduction Low back pain (LBP) is a leading cause of disability and interferes with quality of life and work performance. This research aimed to determine the prevalence and associated factors of LBP among office workers in a public university in Malaysia. Methods This is a cross-sectional study. A self-constructed questionnaire was administered on office workers in Universiti Putra Malaysia, Serdang who have worked for at least 1 year. Workers who were pregnant or known to have back or spine disorder were excluded. Data was analyzed using SPSS version 21.0 for windows. Results We obtained 155 (response rate 81.0%) respondents who were mostly female (78.1%), aged less than 40 years (77.3%), Malays (98.7%) and never attended office ergonomics course (90.3%). Prevalence of LBP was 37% where majority were female (78.9%), Malay (98.2%), young (80.7%) and had poor knowledge on office ergonomics(62.5%). LBP was highest among those who worked for 10 years or less (66.1%), not attended office ergonomics course (91.2%), used non-ergonomic chair (98.2%) and leave their working chair infrequently (62.5%) and in short duration (74.1%). However, there were no statistically significant association for the factors (p>0.05). Discussion Low back pain affects more than one third office workers in UPM who are generally young, relatively new and those who have never attended office ergonomics course. All office workers should be trained on office ergonomics. The management should provide a conducive environment for good office ergonomics in order to prevent and control the occurrence of low back pain among office workers.